2020
DOI: 10.3390/ijms21186709
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Characterization, and Genomic Analysis of Novel Serratia Temperate Phages from a Gold Mine

Abstract: Bacteria of the genus Serratia inhabit a variety of ecological niches like water, soil, and the bodies of animals, and have a wide range of lifestyles. Currently, the complete genome sequences of 25 Serratia phages are available in the NCBI database. All of them were isolated from nutrient-rich environments like sewage, with the use of clinical Serratia strains as hosts. In this study, we identified a novel Serratia myovirus named vB_SspM_BZS1. Both the phage and its host Serratia sp. OS31 were isolated from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 116 publications
(127 reference statements)
3
16
0
Order By: Relevance
“…The virus was sensitive to temperatures ≥ 40 • C, with an immediate loss of infectivity at 50 • C (Figure 5). A similarly limited tolerance to higher temperatures was previously demonstrated for the temperate Serratia phage BZS1 isolated from the same environment, but from rock biofilms [16]. However, the stable low temperature in this gold mine (10-11 • C) [9,10] is probably sufficient for the propagation and survival of these viruses.…”
Section: Comparative Genomic Analysessupporting
confidence: 67%
See 4 more Smart Citations
“…The virus was sensitive to temperatures ≥ 40 • C, with an immediate loss of infectivity at 50 • C (Figure 5). A similarly limited tolerance to higher temperatures was previously demonstrated for the temperate Serratia phage BZS1 isolated from the same environment, but from rock biofilms [16]. However, the stable low temperature in this gold mine (10-11 • C) [9,10] is probably sufficient for the propagation and survival of these viruses.…”
Section: Comparative Genomic Analysessupporting
confidence: 67%
“…(MBQ3883869.1) and Snodgrassella alvi (RZA00671.1), with 34% sequence identity (Figure S4). By following a previously described procedure [16], we confirmed that GATC sequences are, in fact, substrates for the KASIA_p114 modification protein (Figure S5). Bacterial Dam-like MTases are responsible for a variety of functional roles, including the regulation of DNA replication and segregation, mismatch repair, and the con-trol of gene expression [62].…”
Section: Genomic Analysis Of the Vb_ssps_kasia Phagesupporting
confidence: 61%
See 3 more Smart Citations